International Tourism, Higher Education and Economic Growth: The Case of North Cyprus - Katircioglu, Salih Turan (Wiley, 2010)
This study investigates the long-run equilibrium relationship between international tourism, higher education growth, real income growth and the direction of causality among these variables for the Turkish Republic of Northern Cyprus, which is not recognised by any country other than Turkey. Results reveal that international tourism and higher education are in a long-run equilibrium relationship with real income growth; international tourism and higher education have an inelastic, yet positively significant impact on real income growth in the long-run period. Finally, the results of the present study reveal that both the tourism-led growth and the higher education-led growth hypotheses are confirmed for North Cyprus.
Keywords: Empirical-Evidence; Time-Series; Cointegration; Hypothesis; Demand; Causality; Trade; China